Total Quality Management (TQM) in Higher Education: Implementation Challenges in Developing Nations - Ruly Nadian Sari; Abdoulaye Issa; Mariama Seyni (PT. Sinergi Bersahaja Sejahtera, 2026)
Background. The growing demand for accountability, global competitiveness, and institutional performance has driven higher education institutions—particularly in developing countries—to adopt Total Quality Management (TQM) frameworks. However, despite strong policy endorsement, TQM implementation often remains fragmented and compliance-oriented due to structural, cultural, and resource-related constraints. Purpose. This study aimed to examine the key challenges in implementing TQM in higher education institutions across developing countries and to identify the critical determinants that influence the effectiveness of TQM practices. Method. A mixed-methods sequential explanatory design was employed. Quantitative data were collected through surveys involving 387 academic and administrative staff, while qualitative data were obtained from semi-structured interviews with 24 institutional leaders and quality assurance officers. Statistical analyses were used to identify significant predictors, followed by thematic analysis to deepen interpretation of the quantitative results. Results. The quantitative findings revealed that leadership commitment, organizational culture readiness, and resource adequacy significantly predict the effectiveness of TQM implementation, with organizational culture functioning as a mediating factor. Qualitative results further indicated that governance instability, limited financial investment, and resistance to managerial reforms constitute persistent barriers to successful implementation. Conclusion. The study concludes that TQM implementation challenges in developing countries are primarily systemic rather than technical. Effective and sustainable quality enhancement requires integrated alignment among leadership, institutional structures, and organizational culture, as well as context-sensitive adaptation of global quality management models to local higher education realities.